Implementation of Fulfillment of Women Prisoners Rights to Get Decent Food: Case Study on Women's Prison Class IIA Jakarta - Fauzhan Akbar Fhazmie Basha; Megawati Barthos (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Fulfillment of food needs in the Correctional Institutions essential to meet the nutritional needs requirements that are worthy of health and stamina of the body. The purpose of this paper is to describe the Fulfillment of the right to get decent food for female inmates. The method used in this study is normative juridical supported by field research in the form of questionnaires and interviews with informants. It uses the traditional approach as the primary legal material. The research was conducted at the Women's Prison Class IIA Jakarta in January-March 2020. In this study, it was determined that the withdrawal of samples using random sampling techniques as many as 50 respondents. The results showed that the Fulfillment of the right to get food in the Women's Prison Class IIA Jakarta is not good enough. Factors that hinder efforts to fulfill the right to obtain decent food include the quality of food produced and the unqualified nutritionists and cooks in Correctional Institutions. Researchers suggest fulfilling the request to get food for female inmates, employees who have a background in nutritionists and cooks.